Maisy dresses up - Cousins,Lucy (London: Walker Books Ltd, 2011)
In Maisy Dresses Up, Maisy the mouse is getting ready for a costume party. She has fun choosing what to wear and eventually decides to dress up as a butterfly. When she arrives at the party, all her friends are dressed in different creative costumes too like a panda, a wizard, and a cowboy. The story ends with everyone having a great time together. With bright, cheerful illustrations and simple text, the book celebrates imagination, friendship, and the fun of dressing up.
Maisy Dresses Up is a fun and colorful picture book by Lucy Cousins that introduces young readers to the joy of dressing up and imaginative play. In this story, Maisy is invited to a costume party and tries to decide what to wear. Each of her friends also shows up in creative costumes, adding excitement and surprise to the celebration. The book encourages creativity, self-expression, and social interaction through playful storytelling and bold, engaging illustrations. It's perfect for toddlers and preschoolers who enjoy dressing up and exploring different roles through pretend play.
Keywords: Imaginative play; Friendship; Creativity